Simulations for Personnel Selection - Fetzer, Michael.; Tuzinski, Kathy. (Springer New York : Imprint: Springer, 2013)
As a means of assessing job applicants, multimedia simulations are proving an advanced alternative to traditional personnel tests. But these technological hiring tools are not without their challenges. Can they adequately balance hard knowledge with necessary soft skills? Do they truly measure what is required of the job? Simulations for Personnel Selection surveys the diversity of this fast-moving field, analyzing key issues in technology, design and development, and scoring and validation. Accessible to the non-technical reader as well as the expert, the book provides both context for effectively implementing simulations and real-world examples of their use in testing for a variety of jobs and industries. Research findings and practical guidelines range widely, from data on candidates' reactions to simulations, to tools available to developers, to considerations for enlisting ready-to-use simulations instead of creating new ones from scratch. "Simulations in Action" chapters home in on specific skill areas across the career landscape, including: Designing and implementing software and computer skills simulations. Measuring contact center skills with multimedia simulations. Interactive simulations in manufacturing settings. Simulations for service roles. Managerial simulations. Tracing cognition with assessment center simulations. Equally lavish in technological, scientific, and business insights, Simulations for Personnel Selection is a prime resource for academics, researchers, educators and professionals in industrial-organizational psychology, and for human resource executives, managers, and professionals. Academics in business and education should find it a valuable addition to their curricula as well.